Contrast Enhancement Image Processing Technique On Segmented Pap Smear Cytology Images. - Mat Isa, Nor Ashidi; Mashor, Mohd Yusoff; Othman, Nor Hayati (2003)

(untitled)
Contrast is one of the factors that influence the accuracy of interpretation of cervical cancer cells on Pap smear images by pathologist. Blur and highly affected by unwanted noise on Pap smear images could give rise in false diagnosis rate.